Comparison of the effect of high fruit and soybean products diet and standard diet interventions on serum uric acid in asymptomatic hyperuricemia adults: an open randomized controlled trial. (2nd April 2016) - Zhang, Meilin; Gao, Yuxia; Wang, Xuan; Liu, Weiqiao; Zhang, Yuwen; Huang, Guowei
Abstract: The aim of this study was to compare the effect of high fruit and soybean products diet and standard diet interventions on serum uric acid (SUA) in asymptomatic hyperuricemia adults. A total of 187 Chinese adults (20–59 years old) with asymptomatic hyperuricemia participated in this randomized trial and were assigned to receive the standard diet recommended by guideline (group 1) and high fruit and soybean products diet (group 2) for 3 months. The outcome of SUA was assessed before and at the end of the intervention period. After 3 months, the SUA in group 1 and group 2 was significant reduced, whereas the SUA was not significantly changed in-between groups. These data suggest that over a 3-month period, although the high fruit and soybean products diet and standard diet interventions yield no different effects on SUA, the high fruit and soybean products dietary intervention could be an effective alternative to a standard diet for achieving clinically important reductions in SUA for asymptomatic hyperuricemia patients.